Valorization of surplus onion for the development and characterization of antioxidant-rich gummies - Krishnan Abinaya; Kumar Sharmila; Santhanvelayudham Priya; Marimuthu Ponmozhi; Radhakrishnan Linekha (Food Hydrocolloids for Health, 2023)
Allium cepa is an herbaceous biennial plant cultivated for its edible bulb and the elementary ingredient in Indian cooking. The surplus onion presents a huge loss due to drying rotting, sprouting, fungal damage, etc. Formulating an onion gummy is a rich source of antioxidants that can promote healthy living and prevent diseases. Our study developed an antioxidant-rich gummy using red onion transforming its pungent taste using tamarind. The gummy samples were subjected to physicochemical analysis where the pH of the samples was in the range of 5.64 to 5.51, the moisture and sugar content ranged from 59.6 to 57.9 and 60.97 to 59.10 respectively, the texture properties of the gummy jelly showed hardness in the range from 571.81±0.2 to 378.26±0.9 g, chewiness from 1,819.1 ± 64.22 to 1,390.9 ± 56.7 g, adhesiveness from 57.4 ± 1.33 to 58.6 ± 1.55, and springiness from 48.78±0.2 to 40.73±0.4 and finally the chromaticity values (L*, a*, and b*) of gummy jelly were, lightness in the range from 7.78±0.08 to 5.83±0.08, redness from 3.39±0.10 to 0.54±0.08 and yellowness from 1.65±0.05 to 1.27±0.05. The antioxidant activity was analyzed using DPPH and ABTS radical scavenging activity and was in the range of 29.75 to 78.85% and 18 to 62% respectively. The sensory evaluation showed that buying intention was highly ranked followed by appearance, taste, flavor, overall preference, and texture. In this study, we conclude that the antioxidant-rich red onion gummy jelly (ROGJ) developed with potential antioxidant activity can be commercialized and could be a healthy substitute for commercial unhealthy gummy jellies.